Fear of falling in the elderly in a hospital setting: scoping review protocol - Capela Oliveira, Ana Rita (2023)
Introduction The expected changes in an aging process contribute to the increased risk of falling and influence the person's own assessment of their risk of falling. In addition to physical injuries, falls can have psychological consequences, such as fear of falling. This concept was defined as a continuous concern of an individual, when standing or walking, with the occurrence of falls, compromising the performance of daily activities. In this sense, the fear of falling is a sensitive human response to nursing care. As health professionals, nurses should consider evaluating the fear of falling and understand how this phenomenon manifests itself in the elderly. Objective Mapping the available scientific evidence related to the fear of falling in the elderly in a hospital environment. Inclusion criteria Quantitative, qualitative, or mixed studies will be considered, as well as systematic reviews and grey literature. The review will include studies on the fear of falling in elderly people who are in hospitals. Methods Scoping review protocol according to the Joanna Briggs Institute method. Three-phase research strategy that will aim to locate published and unpublished studies in Portuguese, English and Spanish. Temporal, geographic, or cultural limits will not be considered in the research. The search strategy will be adapted to each database/repository in order to identify relevant studies. The selection of studies will begin by analysing the title and abstract. The full text of the selected studies will be analysed by two independent reviewers who will extract data using a specific instrument. The protocol was registered on the Open Science Framework platform (DOI - https://doi.org/10.17605/OSF.IO/B5V6K).